The Parameters Comparison of the “Starlink” LEO Satellites Constellation for Different Orbital Shells - Cakaj, Shkelzen (Frontiers in Communications and Networks, 2021)
Communications integrated satellite-terrestrial networking towards providing global internet broadband services recently reflects the highest research scientific and industry interests worldwide. The most convenient structure for such approach are Low Earth Orbit (LEO) satellites because of the shorter distance from the Earth compared to the other orbits, and consequently seriously lower latency. Among these efforts is the Starlink satellite constellation. Starlink is a satellite constellation designed by the US Company SpaceX. The constellation is planned to consist of thousands of small Low Earth Orbit satellites dedicated to maximize the broadband internet services towards the global Earth coverage, combined with ground stations as a part of satellite-terrestrial integrated network. By 24 October 2020, 893 satellites are accommodated in orbits of altitude of 550km under different inclinations, determining the first Starlink orbital shell. Two next generations are planned to be suited at altitudes of 1110km and 340 km, completing the appropriate infrastructure of three Starlink satellite shells, towards ubiquitous presence of broadband internet service. These three orbital shells manifest different space views seen from the ground station (user), because of their different altitudes, thus through this paper are compared a few parameters which describe the satellite’s behavior considered from the ground station’s ( user’s) point of view. These parameters in fact stem from the space orbital parameters and are defined as: horizon plane wideness, slant range, latency and coverage area. The comparison is given for the three Starlink orbit layers, with identification of appropriate drawbacks and advantages, as performance indicators. By the end, these parameters are applied to geometrically interpret and confirm the handover process among satellites. This paper may serve to trigger the new challenges of the satellite-terrestrial integrated network, providing some theoretical analysis and performance comparisons for the satellites in different orbit layers seen from the ground station (user) perspective.